The The role of leadership communication and organizational communication satisfaction in improving librarians' agility - Rachmani, Ira Dwi; Sarwoprasodjo, Sarwititi; Muljono, Pudji; Pertamasari, Riko Bintari (Record and Library Journal, 2025)
Background of the study: In the VUCA era, librarians must have an agile character, namely the ability to be proactive, adapt quickly, remain resilient in the face of unexpected changes, and be innovative in performance Purpose: This study aims to investigate the influence of leadership communication on the agility of librarians working in special libraries within the scope of the Ministry of Agriculture. Method: Using a high-order construct model, Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze data collected from 103 librarians via the survey method. Findings: The result of this study showed a significant influence of leadership communication on librarians' agility mediated by librarians' communication satisfaction. Conclusion: This study emphasizes the importance of leadership communication and a good communication climate in the library unit in the Ministry of Agriculture to create communication satisfaction that increases the agility of librarians.